2020
DOI: 10.1016/s2213-2600(20)30325-8
|View full text |Cite
|
Sign up to set email alerts
|

Time-varying intensity of mechanical ventilation and mortality in patients with acute respiratory failure: a registry-based, prospective cohort study

Abstract: Background Mortality in acute respiratory failure remains high despite the use of lung-protective ventilation. Recent studies have shown an association between baseline ventilation parameters (driving pressure or mechanical power) and outcomes for patients with acute respiratory distress syndrome. Strategies focused on limiting these parameters have been proposed to further improve outcomes. However, it remains unknown whether driving pressure and mechanical power should be limited over the entire duration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
124
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(155 citation statements)
references
References 28 publications
12
124
1
3
Order By: Relevance
“…The median [IQR] day 1 sequential organ failure assessment score was 6 [3][4][5][6][7]. Invasive mechanical ventilation (IMV) was used in 57% of patients for a median [IQR] of 11 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] mL/ cmH 2 O) and very elevated estimated dead space fraction (day 1 = 0.60 [0.53-0.67]; day 10 = 0.72 [0.69-0.79]). Overall hospital mortality was 25%, and 21% in the IMV patients.…”
mentioning
confidence: 99%
“…The median [IQR] day 1 sequential organ failure assessment score was 6 [3][4][5][6][7]. Invasive mechanical ventilation (IMV) was used in 57% of patients for a median [IQR] of 11 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] mL/ cmH 2 O) and very elevated estimated dead space fraction (day 1 = 0.60 [0.53-0.67]; day 10 = 0.72 [0.69-0.79]). Overall hospital mortality was 25%, and 21% in the IMV patients.…”
mentioning
confidence: 99%
“…These variables were chosen because they were commonly used for assessing disease severity as was used in the sequential organ failure assessment (SOFA) score. MP was calculated as follows [ 14 , 26 ]: where TV is the tidal volume and is the peak inspiratory pressure and is the end-inspiratory plateau pressure. Missing values were imputed by the Last observation carried forward (LOCF) method for longitudinal data [27] , sensitivity analysis by using hot deck method was performed to ensure stability of the results (results not shown) [28] .…”
Section: Methodsmentioning
confidence: 99%
“…These variables were chosen because they were commonly used for assessing disease severity as was used in the sequential organ failure assessment (SOFA) score. MP was calculated as follows [14,26]:…”
Section: Variablesmentioning
confidence: 99%
“…The simplified version of this calculation allows one to estimate mechanical power with only V T , respiratory rate, peak pressure and ΔP [21], and day 1 mechanical power calculated in this manner has been associated with mortality [22]. Furthermore, a recent analysis of a large registry of over 13,000 patients with hypoxemic respiratory failure showed that exposure to higher intensity of mechanical ventilation (higher driving pressure or mechanical power), even for relatively brief periods, was independently associated with increased mortality over the entire duration of ventilation; with stronger association in those with worse baseline hypoxemia [23]. Nevertheless, randomized trials demonstrating the superiority of a ventilatory strategy focused on limiting driving pressure or mechanical power are still needed, and a recent small trial (n = 31) suggest a ΔP-limited strategy may be feasible [24].…”
Section: Evolving Standardsmentioning
confidence: 99%